2017
DOI: 10.1097/mco.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Altered satellite cell dynamics accompany skeletal muscle atrophy during chronic illness, disuse, and aging

Abstract: Purpose of review This review explores recent research investigating the contribution of satellite cells (skeletal muscle stem cells) during muscle fiber atrophy as seen in periods of disuse, illness and aging. Recent findings Studies indicate reduced satellite cell activity and density in a variety of acute and chronic conditions characterized by robust muscle wasting. The direct contribution of satellite cells to unloading/denervation and chronic illness-induced atrophy remains controversial. Inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…A reduced number of SCs and an inability to undergo myogenesis may be the outcome of, or contribute to skeletal muscle disorders such as atrophy, cachexia and sarcopenia [4]. In this regard, it has been the aim of many scientists to optimize myogenesis in-vitro to improve therapies to alleviate symptoms associated with muscle atrophy and degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced number of SCs and an inability to undergo myogenesis may be the outcome of, or contribute to skeletal muscle disorders such as atrophy, cachexia and sarcopenia [4]. In this regard, it has been the aim of many scientists to optimize myogenesis in-vitro to improve therapies to alleviate symptoms associated with muscle atrophy and degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite cells (also known as skeletal muscle stem cells) are the precursors of skeletal muscle cells required for muscle mass maintenance and muscle regeneration following muscle atrophy (70). Previous studies have demonstrated the alterations of satellite cell activity and density by muscle catabolic conditions, such as disuse and ageing (71). Indeed, Yoshihara and co-authors (34) also revealed that the protection against disuse muscle atrophy exerted by astaxanthin might be due to the increase in satellite cell numbers.…”
Section: The Mechanism Of Action Of Astaxanthinmentioning
confidence: 99%
“…ubiquitin‐proteasome [UPP] and autophagy) and decrease in protein synthesis . Myogenic precursors, including SCs, also might contribute to the maintenance of skeletal mass in health and diseases, and recent work has shown that atrophy factors inhibit their regenerative and fusion potential …”
Section: Rage and Skeletal Muscle Atrophymentioning
confidence: 99%